The homosexual advance defence in Australia: an examination of sentencing practices and provocation law reform - McGeary, Rebecca (The Australian and New Zealand journal of criminology, 2018)
In May 2015, the judgment of the High Court of Australia in Lindsay v The Queen reignited debate surrounding the use of the partial defence of provocation in cases involving a non-violent homosexual advance. Lindsay re-established the legal possibility that a man provoked enough to lose self-control and commit lethal violence in response to a non-violent homosexual advance could be convicted of manslaughter by reason of provocation rather than murder. The judgment arrived in the midst of two decades of national law reform activity, whereby all Australian jurisdictions have either introduced or proposed reform to abolish or restrict the application of the controversial partial defence of provocation. In doing so, cases involving a homosexual advance defence are increasingly shifting to the realm of sentencing. This article offers a timely analysis of the sentencing of homosexual advance defence cases in New South Wales and Queensland. In doing so, it examines the judicial treatment of a defendant’s claim of a ‘special sensitivity’ to a homosexual advance, problems arising from the private nature of an alleged homosexual advance and the treatment of intoxication in sentencing. It reveals that reform of legal categories alone may not be sufficient in ensuring a just legal response to homicides incited by alleged homosexual advances.